Penyelesaian Tindak Pidana Ringan Oleh Kepolisian Daerah Gorontalo: Respon terhadap Peraturan Mahkamah Agung Nomor 2 Tahun 2012 - Zumiyati Sanu Ibrahim (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Institut Agama Islam Negeri Sultan Amai Gorontalo, 2017)
This study discusses the adjustment of minor criminal offenses and the amount of fines in the Criminal Code in the investigation process by the Gorontalo Regional Police. This type of research is descriptive qualitative using a juridical and empirical approach. Data was collected through an interview, observation and documentation process. The results showed that the Supreme Court Regulation No. 2 of 2012 concerning Adjustment of Limits of Minor Crimes and the Amount of Fines in the Criminal Code, has been implemented and applied in the resolution of minor criminal offenses in Gorontalo, where the Police Investigators in the Gorontalo Regional Police have a good response and welcome positively the regulation.